Chief Anotklosh of the Taku, Alaska, ca. 1913 - Case, W.H. (William Howard)
The Taku are a group of nothern Tlingit whose traditional lands extended along the Taku River and included the area northeast of Juneau, Alaska. Chief Anotklosh wears a woven Chilkat blanket made from cedar bark and mountain goat wool which had been dyed yellow, black and blue-green. He holds a carved wooden bird rattle and wears a European military-style cap. The northern Tlingit carried on a lively trade with merchant vessels and bartered for large numbers of imported goods. Caption on image: "Chief Anotklosk Chief of the Taku Tribe, Juneau, Alaska." Photographer W.H. Case went to Skagway, Alaska in 1898. He photographed in Sitka, Juneau and other locations, and died in Juneau in 1920. Between 1898 and 1908, Case was in partnership with Horace H. Draper in the firm of Case & Draper. When the partnership dissolved in 1908, Case took charge of the Juneau studio. He died in 1920. (University of Washington Special Collections, from information supplied by the Alaska State Historical Library)